Effects of Land Fragmentation on Productivity in Northwestern Ethiopia - Gashaw Tenna Alemu; Zewdu Berhanie Ayele; Assefa Abelieneh Berhanu (Advances in Agriculture)
Generally, land fragmentation is a universal trait of all agricultural systems which affects farmland productivity and no one had documented a rural society where there was no land fragmentation. Hence, this study sought to ascertain the effects of land fragmentation on farmland productivity in the highland districts of Northwestern Ethiopia by using cross-sectional data collected from 240 respondents during 2015/16 production seasons and analyzed by using linear and Cobb-Douglass production functions. In land productivity model, 38% of variations in farmland productivity are explained by variations in independent variables including land fragmentation parameters. Average farmland size of 1.25 ha was obtained as minimum size that can generate minimum food and cash requirement of an average family of five adult equivalents. Hence, the government should come up with land use policy and population growth controlling program, which enables determining minimum economic farmland size, improving land productivity, and finding ways to strengthen off-farm activities and livestock sector to absorb more labor and enhance means of generating more income so as to decrease minimum farmland size required.